2020
DOI: 10.1007/s10309-020-00384-y
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the visual system—from the optic chiasm to primary visual cortex

Abstract: Epilepsy surgery is a well-established method of treatment for pharmacoresistant focal epilepsies, but it carries an inherent risk of damaging eloquent brain structures. This holds true in particular for visual system pathways, where the damage to, for example, the optic radiation may result in postoperative visual field defects. Such risk can be minimized by the identification and localization of visual pathways using diffusion magnetic resonance imaging (dMRI). The aim of this article is to provide an overvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Effectively, it is unknown which anatomical features of the chiasm may be employed in an individualized detection of malformations or whether such a detection is possible in the first place. Recently, the application of anatomy-sensitive diffusion MRI (dMRI), capable of estimating the proportion of crossing and non-crossing nerves via tractography ( Puzniak et al, 2021 ), has demonstrated chiasmal malformations in albinism at the group level ( Ather et al, 2018 ) with potential for an individualized diagnostic utility ( Puzniak et al, 2019 ). It must be noted, however, that dMRI as compared to aMRI is time consuming at the level of both data acquisition and data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Effectively, it is unknown which anatomical features of the chiasm may be employed in an individualized detection of malformations or whether such a detection is possible in the first place. Recently, the application of anatomy-sensitive diffusion MRI (dMRI), capable of estimating the proportion of crossing and non-crossing nerves via tractography ( Puzniak et al, 2021 ), has demonstrated chiasmal malformations in albinism at the group level ( Ather et al, 2018 ) with potential for an individualized diagnostic utility ( Puzniak et al, 2019 ). It must be noted, however, that dMRI as compared to aMRI is time consuming at the level of both data acquisition and data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by Puzniak et al (2021), to perform tractography of the visual system, the individual structures of optic chiasm, LGN, and V1 need to be provided at least. In our case, the locations of these structures were estimated automatedly as outlined above.…”
Section: Probabilistic Tractographymentioning
confidence: 99%